2022
DOI: 10.13057/biodiv/d230712
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Evaluation of F6 generation of upland rice promising lines for drought stress tolerance

Abstract: Abstract. Mustikarini ED, Lestari T, Santi R, Prayoga GI, Cahya Z. 2022. Short Communication: Evaluation of F6 generation of upland rice promising lines for drought stress tolerance. Biodiversitas 23: 3401-3406. Water is important in metabolic processes affecting rice crop growth and development. Drought stress can decrease rice production, necessitating the development ofdrought-tolerant varieties. Selection of drought-tolerant can be done during the critical period plant booting phase. Thisresearch aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Trace element and water deficit during the initiation period of the panicle can result in a not fully developed panicle which can affect the future grains. The characteristic of the number of filled grains in a panicle is determined by the generative phase starting from the flowering and fertilization process (Mustikarini et al, 2022).…”
Section: The Number Of Filled Grains Per Paniclementioning
confidence: 99%
“…Trace element and water deficit during the initiation period of the panicle can result in a not fully developed panicle which can affect the future grains. The characteristic of the number of filled grains in a panicle is determined by the generative phase starting from the flowering and fertilization process (Mustikarini et al, 2022).…”
Section: The Number Of Filled Grains Per Paniclementioning
confidence: 99%
“…Some studies reported an increase in root length under drought stress compared to well-watered conditions (Baccari et al 2020;Chun et al 2021). Other studies, on the other hand, reported no significant difference in root length between plants exposed and not exposed to drought stress conditions (Mustikarini et al 2022). The decrease in root length under drought stress conditions is caused by a decline in both cell division and cell expansion (Yusuf and Hamed 2021) and limited distribution of assimilate to root organs, resulting in shorter root length.…”
Section: Level Gmentioning
confidence: 99%
“…Drought stress in the flowering phase caused a reduction in pollen count per stigma, pollen viability, and pollen germination rate (Gang-Shun et al 2018). To overcome this problem, selecting rice genotypes tolerant to drought stress (Oladosu et al 2016;Huang et al 2019;Mustikarini et al 2022) is necessary. Increasing grain yield under drought stress conditions is an important breeding goal (Heinemann et al 2019;Sabouri et al 2022).…”
Section: Introductionmentioning
confidence: 99%